Fungsi Kognitif Penderita Diabetes Mellitus Pra-Lansia dan Lansia di Puskesmas Kalumata - Saputra, Sadrakh Dika; The, Fera; Hidayat, Ferdian (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2024)
Almost every country is experiencing an increase in the number of elderly people. As weage, individuals become more susceptible to Diabetes Mellitus / DM. One of thecomplications of DM is cognitive impairment that threatens the welfare of the elderlypopulation. The purpose of this study is to determine the relationship between DM andcognitive function of pre-elderly and elderly patients. This study is a cross sectional researchwith accidental sampling techniques on samples amounted to 97 samples and used medicalrecords to determine DM status and Mini Mental State Examination questionnaire to assesscognitive function of the sample. The sample in this study was dominated by patients aged 45-59 years (63,9%), female gender (58,8%), Junior High School (25,8%). There were 62 pre-elderly patients with 17 people (27,4%) have Mild Cognitive Impairment / MCI, and 35elderly patients with 20 people (57,1%) have MCI. The result of chi-square test obtained a p-value = 0,000 indicating that DM has a significant relationship with cognitive function andan OR value of 5,27, which means that DM patients are at risk of 5,27 times greater forcognitive impairment compared to non-DM patients.